How Does Exam Anxiety Affect the Performance of University Students? - Trifoni, Anisa; Shahini, Miranda (Richtmann Publishing, 2011)
The work of assessing studentsâ€™ learning is complex. In order to assess their work objectively, teachers and instructors usevarious methods and instruments, one of which is testing. We are aware that nowadays testing has become an inherent part of the societywe live in. Consequently, many important decisions are based on test results. So, it is not surprising that anxiety during tests has becomea prominent problem in schools all over the world. The present study focuses primarily on test anxiety and its impact on learning, as wellas its causes and effects on students. A test anxiety scale followed by a set of questions was completed by a sample group of undergraduatestudents of â€œAleksandÃ«r Moisiuâ€ University. The results indicated that a considerable number of students were affected, at least at somedegree, by test anxiety. From this perspective, the following questions are raised: â€œWhat causes test anxiety?â€ and â€œWhat can be done toalleviate this problem?â€ The findings of this empirical study, the review of literature as well as students experiences provide usefulsuggestions concerning the ways of alleviating test anxiety.